MENGAMATI KESELAMATAN PENUMPANG ANGKUTAN SUNGAI DAN DANAU - Susilo, Budi Hartanto; Elsha, Petrus Teguh (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Accident rate of the rivers and lakes transport in Indonesia is still quite high. This is due to lack of transportation eligibility level. The human factors that often ignores existing safety standards. Additionally socialization in safety awareness was minimum in the absence of transport resulting in omission of the rivers and lakes transport user. From the observations in the province of North Sumatra , South Sumatra , South Kalimantan , and Bali, every region has turned out to have local legislation and regulations to cope with a hazard transport streams and lakes with different technical terms , the depth and breadth of regulations including licensing different. On the other hand have the same orientation that permits transport in rivers and lakes (ASD ) is a PAD (the original income) so that the rigor in the application of ASD to be weak safety, such as the use of life jackets, navigation tools, and others.